Weird, Weather/ RAIN OR SHINE, LIGHTNING OR FLOODS, WEATHER IS AWESOME - OLIVER, Clare (Britain; Ticktok, 2006)
Journey into the Earth's atmosphere to discover cottonwool clouds, hurricane killers and wicked winds.
Includes index, quiz answers